2021
DOI: 10.1098/rsta.2021.0126
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the geographical spread of HIV among MSM in Guangdong, China: a metapopulation model considering the impact of pre-exposure prophylaxis

Abstract: Men who have sex with men (MSM) make up the majority of new human immunodeficiency virus (HIV) diagnoses among young people in China. Understanding HIV transmission dynamics among the MSM population is, therefore, crucial for the control and prevention of HIV infections, especially for some newly reported genotypes of HIV. This study presents a metapopulation model considering the impact of pre-exposure prophylaxis (PrEP) to investigate the geographical spread of a hypothetically new genotype of HIV among MSM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
(44 reference statements)
0
4
1
Order By: Relevance
“…This finding explains why this study's monitoring/evaluation of HIV/AIDs prevention programmes suggested a high extent. The findings, however, contradict other studies that documented that the rising frequency of sexually transmitted illnesses, especially HIV/AIDS, demonstrates that previous attempts to combat the pandemic have been insufficient, even with antiretroviral therapy (Kalichman, Eaton, and Kalichman 2021;Mosha et al 2022;Jing et al 2022;Thitipatarakorn et al 2022). The disparity in results might be related to variations in the factors included in the investigations.…”
Section: Discussion Of Findingscontrasting
confidence: 84%
“…This finding explains why this study's monitoring/evaluation of HIV/AIDs prevention programmes suggested a high extent. The findings, however, contradict other studies that documented that the rising frequency of sexually transmitted illnesses, especially HIV/AIDS, demonstrates that previous attempts to combat the pandemic have been insufficient, even with antiretroviral therapy (Kalichman, Eaton, and Kalichman 2021;Mosha et al 2022;Jing et al 2022;Thitipatarakorn et al 2022). The disparity in results might be related to variations in the factors included in the investigations.…”
Section: Discussion Of Findingscontrasting
confidence: 84%
“…Another area for future research is how to incorporate interventions into the model. This could be done by dividing the individuals with HIV into asymptomatic and symptomatic individuals and treating symptomatic individuals as in Salman 20 or dividing these individuals into more classes, including those on PrEP and antiretroviral therapy as in Jing et al, 17 in order to model these treatments. There are many other papers modeling HIV interventions, including Zhang et al, 15 Babaei et al, 13 Gountas et al, 18 Des Jarlais et al, 14 and Flountzi et al 45 and these give other options for modeling HIV interventions.…”
Section: Discussionmentioning
confidence: 99%
“…and note (17) is the rate at which infected PWIDs visit infected needles and leave the needles uninfected. This completes our interpretation of Equations ( 15) and ( 16).…”
Section: Development Of Greenhalgh and Hay's Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Human mobility also plays a crucial role in the spread of HIV among at-risk populations, such as men who have sex with men (MSM). Dan Wu and colleagues characterized the behavioural dynamics underlying the spread of HIV within and between cities in Guangdong province, China, by harnessing the multi-sourced big data from MSM social networking sites, offline human mobility network, and self-reported sexual behaviours among MSM [ 4 ]. Their study demonstrated that the adoption of pre-exposure prophylaxis (PrEP) by MSM significantly delayed the occurrence of HIV in all cities.…”
mentioning
confidence: 99%